Re-Reading “Greenes Groatsworth of Wit” - Sawyer, Robert (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2012)
This essay focuses on the alleged attack by Robert Greene on Shakespeare as an “upstart crow,” a work reprinted in almost every collection of Shakespeare’s works, and a document that has produced its own body of scholarly assessment. Employing recent textual criticism of the print industry in early modern England —including works by Zachary Lesser, John Jowett, Jeffery Masten, and D. Allen Carroll— we re-read “Green’s Groatsworth of Wit” as a kind of literary criticism that helps to illuminate both its own textual status as well as the material conditions of the late sixteenth-century theatrical world which produced it. Following a review of the basic lines of interpretation of the piece, I examine the nexus of the Henry Chettle, Robert Danter and Greene connection, in an attempt to show that by considering the “collaboration” between these three, we should come to a better understanding of the document itself. Equally important, by re-examining the text, reviewing the printing process, and rethinking the authorial voice of the work, I hope to re-situate the pamphlet’s place in the present debate on Shakespeare and his contemporaries.